PENGARUH PERMAINAN BOY-BOYAN UNTUK MENINGKATKAN MINAT SISWA PUTRI DALAM PEMBELAJARAN SEPAKBOLA KELAS VII SMPN 1 CILAMAYA WETAN - Afiat, Intan; Asep Suherman; Nana Suryana Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of the researcher in making this thesis is to answer the formulation of the problem in the study, namely the problem in this study is "Is There an Effect of Boy-boyan Games on Increasing Interest in Learning Soccer in Female Students of Class VII of SMPN 1 Cilamaya Wetan?" The problem of this study is the lack of interest in playing in female students so that the female students are lazy, less enthusiastic, feel unhappy and less confident when participating in soccer learning, especially when doing basic movement skills, this study is a quantitative study with a pre-experimental method and using one group pretest-posttest design. The sampling technique uses a purposive sampling technique. The instruments used are questionnaires and Likert scales. There are three stages in this study, namely pretest, treatment and posttest. Treatment was carried out 4 times. From the results of the pretest and posttest, an increase was obtained from the initial average of 3.96, a significant value was obtained from the pretest results of 0.096 while the posttest value of 0.740 from these results it is said that both are normally distributed because the significant value is more than 5% or from 0.05.